Personalising drug safety—results from the multi-centre prospective observational study on Adverse Drug Reactions in Emergency Departments (ADRED) - Just, Katja S.; Dormann, Harald; Böhme, Miriam; Schurig, Marlen; Schneider, Katharina L.; Steffens, Michael; Dunow, Sandra; Plank-Kiegele, Bettina; Ettrich, Kristin; Seufferlein, Thomas; Gräff, Ingo; Igel, Svitlana; et al. (European Journal of Clinical Pharmacology, 2020)
Purpose: Adverse drug reactions (ADR) account for 5 to 7% of emergency department (ED) consultations. We aimed to assess medication risk profiles for ADRs leading to ED visits. Methods: We analysed medication intake and patient demographics in a prospective multi-centre observational study collecting ADR cases in four large EDs in Germany. Odds ratios (OR) were calculated to relate drug classes taken to those suspicious for an ADR after a causality assessment. Results: A total of 2215 cases of ED visits due to ADRs were collected. The median age of the cohort was 73 years; in median, six co-morbidities and an intake of seven drugs were documented. Antineoplastic/immunomodulating agents had the highest OR for being suspected for an ADR (OR 20.45, 95% CI 14.54–28.77), followed by antithrombotics (OR 2.94, 95% CI 2.49–3.47), antibiotics (OR 2.65, 95% CI 1.78–3.95), systemic glucocorticoids (OR 2.43, 95% CI 1.54–3.82) and drugs affecting the central nervous system (CNS), such as antipsychotics (OR 2.36, 95% CI 1.46–3.81), antidepressants (OR 2.10, 95% CI 1.57–2.83), antiparkinsonian medication (OR 2.11, 95% CI 1.15–3.84), opioids (OR 1.79, 95% CI 1.26–2.54) and non-opioid analgesics (OR 1.32, 95% CI 1.01–1.72). Conclusions: Patients experiencing ADRs leading to ED visits are commonly old, multi-morbid and multi-medicated. CNS drugs may be more relevant than prior expected. With calculating ORs, we could replicate involvement of antineoplastic agents, antithrombotics, antibiotics, systemic glucocorticoids and non-opioid analgesics as frequently suspected for ADRs in EDs. Trial registration: DRKS-ID: DRKS00008979.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Adverse drug reaction; Drug class; Drug safety; Emergency department; Medication; Older adults